(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Indigenous people actively participate as partners in the conservation of biodiversity, and local places are home to biodiversity. They have extensive understanding of the behavior of complex natural systems in their own communities, where resource-use traditions have persisted historically. Traditional knowledge is the body of information that different societies throughout the world have accumulated over time. Such information has been used and passed down across numerous generations after amassing throughout time. It typically relates to the community’s natural surroundings and includes agricultural knowledge, such as how to cultivate, environmental knowledge, and understanding of herbal remedies. Traditional knowledge incorporates the customary use of biological resources in conformity with traditional cultural practices in its definition of sustainable use of biodiversity. Traditional knowledge of animals, plants, soils, and landscapes for the sustainable use of resources; traditional resource management system with an appropriate set of tools, techniques, and practices; social institutions or organizations for coordination, co-operation, rule-making, and rule enforcement; and finally, environmental perception and gives meaning to social behavior are all considered as roles of traditional knowledge for biodiversity conservation.